Research on Digital Transformation and the Construction of Physical Education Teacher Resource Ecosystem - Gao, Peng; Jing, GuPing (Quality in Sport, 2025)
Against this backdrop, the construction of the teacher resource ecosystem, especially the optimization and reshaping of the physical education teacher resource ecosystem, has become increasingly important and urgent. This study focuses on this, delving into the rich connotations, core components and dynamic evolution characteristics of the physical education teacher resource ecosystem in the context of digital transformation, and dissecting in detail the many practical problems and deep-seated challenges in terms of concepts, technologies, resources and evaluations in the current process of building the physical education teacher resource ecosystem Based on this, we have explored practical approaches and multi-dimensional development strategies. Through systematic theoretical reasoning and practical path analysis, it aims to provide solid theoretical support and powerful practical guidance for effectively improving the quality of education and teaching in the new era, vigorously promoting educational equity and balanced development, and fully advancing the modernization and intelligentization process of education. In order to help the education sector achieve intrinsic and high-quality development in the surging wave of digital transformation, especially in the application of digital technology to enhance physical education teaching skills, to achieve scientific and personalized training guidance, to promote the wider and deeper popularization and implementation of national fitness activities, and ultimately to cultivate more people who have solid professional qualities, With the ability to skillfully use digital tools for teaching innovation and research, we aim to produce high-quality, versatile sports professionals who can better adapt to the strategic needs of national development in the new era.